2020
DOI: 10.1177/1120700020943481
|View full text |Cite
|
Sign up to set email alerts
|

The experimental study of tissue integration into porous titanium implants

Abstract: Introduction: Due to a lack of uniform shapes and sizes of bone defects in hip and knee joint pathology, their fixing could benefit from using individually manufactured 3D-printed highly porous titanium implants. The objective of this study was to evaluate the extent of bone and muscle tissue integration into porous titanium implants manufactured using additive technology. Materials and methods: Porous and non-porous titanium plates were implanted into the latissimus dorsi muscle and tibia of 9 rabbits. On day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Shot peening has been shown to improve the fatigue performance and failure mechanisms of titanium specimens, indicating its potential to enhance the material's mechanical properties [ 15 ]. Furthermore, the experimental study by Tikhilov et al confirmed the possibility of achieving a strong attachment to the bone with a tensile strength of 148 N for porous titanium implants, highlighting the potential for further improving the mechanical properties of titanium through innovative designs and treatments [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shot peening has been shown to improve the fatigue performance and failure mechanisms of titanium specimens, indicating its potential to enhance the material's mechanical properties [ 15 ]. Furthermore, the experimental study by Tikhilov et al confirmed the possibility of achieving a strong attachment to the bone with a tensile strength of 148 N for porous titanium implants, highlighting the potential for further improving the mechanical properties of titanium through innovative designs and treatments [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of material may further enhance osseointegration and construct stability. Both porous tantalum and titanium have been found to show superior osseointegration among common acetabular implant materials in animal studies [ [22] , [23] , [24] , [25] ]. The biocompatibility of titanium has also shown to be more optimal than that of other conventional implant materials such as tantalum or chrome-cobalt alloys, further lending to the acetabular shell’s ability to osseointegrate and remain well-fixed [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on mechanical analysis, the peel strength of tissue attachment was strongest with the coarse plate [ 43 ]. In 2020, Tikhilov et al measured tensile strength of soft tissue by inserting Ti-6Al-4 V plates (20 mm × 7 mm × 3 mm, 100-µm pore size) into the latissimus dorsi muscle of 7-month-old female Chinchilla rabbits for 90 d. The strength of the soft tissue adhesion to the 100-µm-pore plates was higher than that obtained with non-porous plates [ 44 ]. This result emphasizes that surface modification can regulate soft tissue integration onto a metal surface.…”
Section: Discussionmentioning
confidence: 99%